Electrochemical-thermal modeling of phase change material battery thermal management systems: Investigating mesh types for accurate simulations - Yousefi, Elnaz; Ramasamy, Devarajan; Kadirgama, Kumaran; Talele, Virendra; Najafi, Hiwa; Olyaei, Mostafa; Miljkovic, Nenad; Panchal, Satyam (Elsevier, 2025)
Computational techniques have been extensively used in the analysis of heat transfer within battery thermal management systems (BTMS). A fundamental and critical initial step in any numerical analysis is the meshing process, which involves subdividing the geometry into numerous small control volumes, or elements. Here, we investigated the accuracy of the simulated thermal performance of a BTMS using phase change material (PCM) with three different mesh types having: hexahedral, tetrahedral, and polyhedral elements. A detailed electrochemical-thermal model is used for modeling heat generation within a lithium-ion battery. In this model, a pseudo two-dimensional model captures the internal dynamics of the battery and then is integrated with a three-dimensional conjugate heat transfer model. Furthermore, the enthalpy-porosity method is employed for PCM simulation using computational fluid dynamics. Among the three mesh types, the hexahedral mesh demonstrated the closest agreement with experimental data, yielding smooth temperature gradients and PCM liquid fraction contours in post-processing. The polyhedral mesh, while slightly less accurate than the hexahedral mesh, provided a computational advantage, requiring only about a fifth of the elements compared to the hexahedral mesh and a quarter compared to the tetrahedral mesh. This computational efficiency makes the polyhedral mesh the most economical in terms of computational resources. However, tetrahedral mesh, though better suited for complex geometries, exhibited the highest computational cost and produced the least accurate results, making it less favorable for PCM-based BTMS simulations. To further improve the trade-off between computational cost and accuracy, a hybrid mesh configuration is introduced, combining polyhedral and hexahedral elements to enhance simulation efficiency while preserving accuracy.